(untitled) (Global Journal of Science Frontier Research, 2018)
Analysis of datasets available from the literature indicates that, during tropical cyclones at sea, the barometric pressure is approximately negatively linearly related to the wind speed as well as to the wave height. During Hurricane Wilma in 2005, simultaneous meteorological-oceanographic (met-ocean) measurements were made by the National Data Buoy Center (NDBC) at the Data Buoy Station 42056 in the northwestern Caribbean Sea. Further analysis of these datasets showed that, when U 10 ≥ 9 m s -1 during wind seas (when H s /L p ≥ 0.020), H s = 0.43 U 10 -2. Here, parameter H s is the significant wave height (in meters), U 10 is the wind speed (in m s -1 ) at 10 m, L p (= 1.56 T p 2 ) is the dominant wave length (in meters), and T p is the peak wave period (in seconds). Applications of this proposed formula were successful during Hurricane Jose in 2017, Typhoon Russ in 1990 by NDBC Buoy 52009 near Guam, Typhoon Krosa in 2007 by a data buoy near Taiwan, and Typhoon Soudelor in 2015 by Jason -2 altimeter satellite. Also, its applications to rapid estimations of peak wave period, sea-surface currents and storm surge potentials were presented.